Internal Political Developments in Laos 1950 – 1954 and the French Position - Hatem Al- Fahad, Maher Chassib (Opción, 2019)
This paper deals with the internal political developments in Laos during 1950 - 1954, during which time witnessed important political transformations, which had a significant impact on achieving full independence in 1954 and finally getting rid of the domination of French colonialism. This period witnessed the return of most of the Lao Asara movement back to the country and aligned them with the Vientiane government, and the emergence of the Pato Lao movement in 1950, allied with the Viet and anti-Vientiane government. 1952 - 1953 As a result, the Lao Patheit announced the formation of its own govern- ment in the province of Sam Noa in 1953, which revealed to us the weakness of the French and their inability to defend Laos in light of the escalation of Viet attacks. On the other hand, political life in Laos was moving forward steadi- ly. Political parties were first formed in the country from 1950 to 1951, after which elections were held in 1951. It gained full independence, except for some things (mostly military) that were deferred to the Geneva conference. It was revealed during this period that the continued presence of the French in Laos was thanks to American assistance, which played an important role in the convening of the Geneva Conference of 1954, which recognized the full inde- pendence of Laos with Vietnam and Cambodia. And influence the French and expel them, and the exploitation of this influence to serve their goals in light of the repercussions of the Cold War. The research was divided into several axes: 1. Historical introduction to Laos until 1949. 2. Political situation in Laos and the emergence of the Pato Lao Movement (January-August 1950). 3. The Pathet Lao activity and the evolution of the political landscape in the country (August 1950 - November 1952) (4) The entry of the Viet Minh elements into the territory of Laos and the position of the Lao and French Governments thereon; November 1952 - April 1953). 5. Formation of the Lao Free Government and the Lao (Government) and French Positions (April- June 1953) 6. The internal political situation in France and its impact on the signing of the Friendship and Cooperation Agreement (June-October 1953). 7- The escalation of the Viet Minh activity in Laos and the Lao and French positions thereof (December 1953 - March 1954) 8. Political and military situation in Laos and the convening of the Geneva Conference (March - July 1954). 9. Final conclusions.